Tubular IL-1β Induces Salt Sensitivity in Diabetes by Activating Renal Macrophages. Issue 1 (16th May 2022) - Veiras, Luciana C.; Bernstein, Ellen A.; Cao, DuoYao; Okwan-Duodu, Derick; Khan, Zakir; Gibb, David R.; Roach, Arantxa; Skelton, Rachel; Williams, Ryan M.; Bernstein, Kenneth E.; Giani, Jorge F.
Abstract : Background: Chronic renal inflammation has been widely recognized as a major promoter of several forms of high blood pressure including salt-sensitive hypertension. In diabetes, IL (interleukin)-6 induces salt sensitivity through a dysregulation of the epithelial sodium channel. However, the origin of this inflammatory process and the molecular events that culminates with an abnormal regulation of epithelial sodium channel and salt sensitivity in diabetes are largely unknown. Methods: Both in vitro and in vivo approaches were used to investigate the molecular and cellular contributors to the renal inflammation associated with diabetic kidney disease and how these inflammatory components interact to develop salt sensitivity in db/db mice. Results: Thirty-four-week-old db/db mice display significantly higher levels of IL-1β in renal tubules compared with nondiabetic db/+ mice. Specific suppression of IL-1β in renal tubules prevented salt sensitivity in db/db mice. A primary culture of renal tubular epithelial cells from wild-type mice releases significant levels of IL-1β when exposed to a high glucose environment. Coculture of tubular epithelial cells and bone marrow-derived macrophages revealed that tubular epithelial cell-derived IL-1β promotes the polarization of macrophages towards a proinflammatory phenotype resulting in IL-6 secretion. To evaluate whether macrophages are the cellular target of IL-1β in vivo, diabetic db/db mice were transplanted with the bone marrow of IL-1R1 (IL-1 receptor type 1) knockout mice. db/db mice harboring an IL-1 receptor type 1 knockout bone marrow remained salt resistant, display lower renal inflammation and lower expression and activity of epithelial sodium channel compared with db/db transplanted with a wild-type bone marrow. Conclusions: Renal tubular epithelial cell-derived IL-1β polarizes renal macrophages towards a proinflammatory phenotype that promotes salt sensitivity through the accumulation of renal IL-6. When tubular IL-1β synthesis is suppressed or in db/db mice in which immune cells lack the IL-1R1, macrophage polarization is blunted resulting in no salt-sensitive hypertension.